2003
DOI: 10.1029/2002wr001596
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and removal of naphthalenesulphonic acids by means of adsorption and ozonation catalyzed by activated carbon in water

Abstract: [1] Studies were conducted on the efficiency of systems based on the use of ozone, activated carbon, and ozone/activated carbon in the treatment of waters containing 1-naphthalenesulphonic acid, 1,5-naphthalenedisulphonic acid, and 1,3,6-naphthalenetrisulphonic acid. In the removal of these acids by adsorption on activated carbon the elevated heights of the mass transfer zone columns and the low values of the breakthrough volumes indicated that a system exclusively based on the use of activated carbon is not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…After ozone treatment, the basic sites were transformed into acid ones. Carbonyl-and carboxyl-type oxygenated functional groups that predominated on the surface of GAC were the main causes of the development of the negative surface charge on GAC [52]. In this case, ozone treatment on the surface of GAC might increase its polarity, thereby enhancing its electrostatic interactions with the positive charge of organic contaminants in the solution for a higher removal [58,59].…”
Section: Effects Of Surface Modification Of Gac With Ozone On the Remmentioning
confidence: 98%
See 1 more Smart Citation
“…After ozone treatment, the basic sites were transformed into acid ones. Carbonyl-and carboxyl-type oxygenated functional groups that predominated on the surface of GAC were the main causes of the development of the negative surface charge on GAC [52]. In this case, ozone treatment on the surface of GAC might increase its polarity, thereby enhancing its electrostatic interactions with the positive charge of organic contaminants in the solution for a higher removal [58,59].…”
Section: Effects Of Surface Modification Of Gac With Ozone On the Remmentioning
confidence: 98%
“…The reduction of color intensity clearly indicated that there was a direct attack of ozone on the double bonds of GAC (in the chromophoric parts) during the ozone treatment [51]. After ozonation had decomposed the recalcitrant compounds into smaller molecules, the organic materials in the leachate became more easily biodegradable, enabling GAC to easily adsorb the remaining organic materials unchanged during the ozonation [52]. This is one of the advantages of using this combined treatment for the removal of refractory compounds from stabilized leachate.…”
Section: Removal Mechanisms Of Recalcitrant Compounds From Leachate Bmentioning
confidence: 99%
“…It then proceeded in the aqueous phase and accelerated the transformation of ozone into secondary radicals such as hydroxyl radicals ( • OH) 20. On the other hand, several researchers have opined that improved pollutant decomposition occurred not because of the formation of radicals, but because of the surface basicity of activated carbon, which enhances ozone decomposition forming highly oxidative species; even mineral matter present in the carbon as an impurity also plays a major role 28–31. In our study, after filtration, the suspended activated carbon was filtered and desorption of dye molecules was carried out, but no colourant molecule was released.…”
Section: Discussionmentioning
confidence: 84%
“…The Fe 2p 3/2 spectrum for samples C-1 and C-1-ozonated shows a 14% increase in the surface concentration of Fe 2 O 3 on C-1-ozonated. According to these findings, the ozone can attack Fe(II) metal sites on the carbon surface during NTA ozonation, generating Fe(III) by Equations ( 49) and (50). These reactions can also enhance ozone transformation rate into HO • radicals, contributing to the ozonation of NTS.…”
Section: %S / = %Dmentioning
confidence: 90%
“…), Norit; (+), Sorbo; (-) Witco (reproduced from [50] with permission of John Wiley and Sons, 2003).…”
Section: Effect Of the Surface Chemistry Of Acs On Dtz Degradation By Uv/ac Systemmentioning
confidence: 99%